Spatiotemporal Characterization of Human Early Intervertebral Disc Formation at Single‐Cell Resolution - Taifeng Zhou; Yu Chen; Zhiheng Liao; Long Zhang; Deying Su; Zhuling Li; Xiaoming Yang; Xiaona Ke; Hengyu Liu; Yuyu Chen; Ricong Weng; Huimin Shen; et al. (Advanced Science, 2023)
Abstract The intervertebral disc (IVD) acts as a fibrocartilaginous joint to anchor adjacent vertebrae. Although several studies have demonstrated the cellular heterogeneity of adult mature IVDs, a single‐cell transcriptomic atlas mapping early IVD formation is still lacking. Here, the authors generate a spatiotemporal and single cell‐based transcriptomic atlas of human IVD formation at the embryonic stage and a comparative mouse transcript landscape. They identify two novel human notochord (NC)/nucleus pulposus (NP) clusters, SRY‐box transcription factor 10 (SOX10)+ and cathepsin K (CTSK)+, that are distributed in the early and late stages of IVD formation and they are validated by lineage tracing experiments in mice. Matrisome NC/NP clusters, T‐box transcription factor T (TBXT)+ and CTSK+, are responsible for the extracellular matrix homeostasis. The IVD atlas suggests that a subcluster of the vertebral chondrocyte subcluster might give rise to an inner annulus fibrosus of chondrogenic origin, while the fibroblastic outer annulus fibrosus preferentially expresseds transgelin and fibromodulin . Through analyzing intercellular crosstalk, the authors further find that notochordal secreted phosphoprotein 1 (SPP1) is a novel cue in the IVD microenvironment, and it is associated with IVD development and degeneration. In conclusion, the single‐cell transcriptomic atlas will be leveraged to develop preventative and regenerative strategies for IVD degeneration.